A 10-Gene Classifier for Distinguishing Head and Neck Squamous Cell Carcinoma and Lung Squamous Cell Carcinoma - Vachani, Anil; Nebozhyn, Michael; Singhal, Sunil; Alila, Linda; Wakeam, Elliot; Muschel, Ruth; Powell, Charles A.; Gaffney, Patrick; Singh, Bhuvanesh; Brose, Marcia S.; Litzky, Leslie A.; Kucharczuk, John; et al. (Clinical cancer research, 2007)
Purpose: The risk of developing metastatic squamous cell carcinoma for patients with head and neck squamous cell carcinoma (HNSCC) is very high. Because these patients are often heavy tobacco users, they are also at risk for developing a second primary cancer, with squamous cell carcinoma of the lung (LSCC) being the most common. The distinction between a lung metastasis and a primary LSCC is currently based on certain clinical and histologic criteria, although the accuracy of this approach remains in question. Experimental Design: Gene expression patterns derived from 28 patients with HNSCC or LSCC from a single center were analyzed using penalized discriminant analysis. Validation was done on previously published data for 134 total subjects from four independent Affymetrix data sets. Results: We identified a panel of 10 genes ( CXCL13, COL6A2, SFTPB, KRT14, TSPYL5, TMP3, KLK10, MMP1, GAS1 , and MYH2 ) that accurately distinguished these two tumor types. This 10-gene classifier was validated on 122 subjects derived from four independent data sets and an average accuracy of 96% was shown. Gene expression values were validated by quantitative reverse transcription-PCR derived on 12 independent samples (seven HNSCC and five LSCC). The 10-gene classifier was also used to determine the site of origin of 12 lung lesions from patients with prior HNSCC. Conclusions: The results suggest that penalized discriminant analysis using these 10 genes will be highly accurate in determining the origin of squamous cell carcinomas in the lungs of patients with previous head and neck malignancies.